Model Test Study on Overburden Failure and Fracture Evolution Characteristics of Deep Stope with Variable Length - Xinfeng Wang; Youyu Wei; Heyong Yuan; Yiying Zhang; Qiao Zhang; Wengang Liu (Advances in Civil Engineering)
Taking two typical stopes with variable length of working face inclined length from small to large and from large to small as the research object, the stope overburden structure model under different face length conditions is constructed through laboratory similar material simulation test, and the dynamic evolution laws of overburden instability deformation, unloading expansion, and collapse failure of forward and reverse knife handle stopes are analyzed. The three-dimensional perspective technology of parallel network electrical method is used to study the spatial distribution range and fracture development characteristics of overburden internal failure. The research shows that the overburden fracture of stope with variable length has the “time-pace-scale” evolution effect of short-time sudden change, zoning load transfer, and continuous extension. The evolution of roof fracture has experienced the development process of unloading expansion, tensile fracture instability, shrinkage deformation, and closure stability. The rise and fall of resistivity during mining in stope with variable length is closely related to the mining time step. When mining 40 cm, it is the position where the resistivity value changes suddenly. The rise of resistivity in the vertical direction makes the electric field show the transient response characteristics of dynamic expansion and rapid evolution. The development height of water conducting fracture zone of the reverse knife handle working face with the inclined length changing from large to small is slightly larger, the degree of overburden damage is high, and the fracture development is relatively sufficient.